The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1995
DOI: 10.1046/j.1471-4159.1995.64010247.x
|View full text |Cite
|
Sign up to set email alerts
|

Loss of Protein Kinase C‐αβ in Brain of Heroin Addicts and Morphine‐Dependent Rats

Abstract: The biochemical status of human brain protein kinase C (PKC)-a)3 during opiate dependence was studied by means of immunoblotting techniques in postmortem brain of heroin addicts who had died by opiate overdose . In the frontal cortex, a marked decrease (53%, p < 0.05) in the immunoreactivity of PKC-aß was found in heroin addicts compared with matched controls . The loss of PKC-(

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
17
0

Year Published

1997
1997
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(18 citation statements)
references
References 21 publications
(31 reference statements)
1
17
0
Order By: Relevance
“…Furthermore, we found that PKC-␣/␤ isoforms modulate ENT2 function because downregulation of the expression of PKC-␣/␤ but not PKC-␥/ isoforms paralleled the reduction of PKC activity, adenosine uptake, and enhancement of extracellular adenosine concentration. In support of our findings, previous studies also reported that chronic exposure to opiates led to a significant reduction of PKC-␣/␤ isoform expression in the frontal cortex of the human and rat brains (Busquets et al, 1995;Ventayol et al, 1997). Although the present and previous studies clearly show the downregulation of PKC-␣/␤ isoform expression in brain after chronic morphine treatments, how the reduction of PKC-␣/␤ abundance in hippocampal synaptosome is achieved in the hippocampus by morphine remains unknown.…”
supporting
confidence: 90%
See 1 more Smart Citation
“…Furthermore, we found that PKC-␣/␤ isoforms modulate ENT2 function because downregulation of the expression of PKC-␣/␤ but not PKC-␥/ isoforms paralleled the reduction of PKC activity, adenosine uptake, and enhancement of extracellular adenosine concentration. In support of our findings, previous studies also reported that chronic exposure to opiates led to a significant reduction of PKC-␣/␤ isoform expression in the frontal cortex of the human and rat brains (Busquets et al, 1995;Ventayol et al, 1997). Although the present and previous studies clearly show the downregulation of PKC-␣/␤ isoform expression in brain after chronic morphine treatments, how the reduction of PKC-␣/␤ abundance in hippocampal synaptosome is achieved in the hippocampus by morphine remains unknown.…”
supporting
confidence: 90%
“…After slightly washing, the membrane was incubated with anti-ENT1 goat polyclonal antibody (1:50 Santa Cruz Biotechnology, sc-48488), anti-ENT2 goat polyclonal antibody (1:50, Santa Cruz Biotechnology sc-48491), anti-PKC-␣/␤ monoclonal antibody, anti-PKC-␥ rabbit polyclonal antibody (1:10,000, Santa Cruz Biotechnology sc-211), anti-PKC-mouse monoclonal antibody(1:50, Santa Cruz Biotechnology sc-56944) in TBS plus 5% BSA and 0.1% Tween 20, followed by incubation with horseradish peroxidaseconjugated IgG (Calbiochem) as the secondary antibody. Visualization was performed using an ECL (enhanced chemiluminescence) kit (GE Healthcare) for PKC-␣/␤ (Busquets et al, 1995) and PKC-␥, SuperSignal West Dura Extended Duration Substrate (Thermo Scientific) for ENT1/2 and PKC-. Band intensities were quantified by using Quantity One software from Bio-Rad.…”
Section: Immunoblotting Assaymentioning
confidence: 99%
“…In a preliminary study in humans, the abundance of NF-L proteins was also shown to be markedly decreased (47%) in prefrontal cortices from chronic opioid abusers (García-Sevilla et al, 1997a). This study also demonstrated that the opioid modulation of NF-L proteins also occurs in the prefrontal cortex, a brain region that is also a target for the chronic effects of opioid drugs in humans (Escribá et al, 1994;Busquets et al, 1995;Simonato, 1996). Recently, chronic treatment of rats with morphine also induced a marked decrease (49%) in NF-L immunoreactivity in the frontal cortex (Boronat et al, 1998).…”
mentioning
confidence: 53%
“…Somewhat confusingly, an earlier article by Shimohama et al (1998) reported that RACK1 levels were not significantly affected in brains of persons with AD, but this discrepancy may reflect a difference in the brain areas examined RACK1 protein levels are also modulated in parallel with levels of PKC␣ and ␤ in the brains of morphine-treated rats (Escriba and Garcia-Sevilla, 1999). Opiate drugs control the protein expression levels of conventional PKC isozymes in the brain, which may affect the activity of adenylyl cyclase, a principle mediator of opioid receptor signaling (Zhou et al, 1994;Busquets et al, 1995;Ammer and Schulz, 1997). This strong positive correlation between the levels of RACK1 and both PKC␣ and ␤ has not been found for other proteins involved in opioid signal transduction, such as G ␣ , G ␤ , GRK2, adenylyl cyclase, and PKA (Nestler and Tallman, 1988;Terwilliger et al, 1994;Escriba and Garcia-Sevilla, 1999).…”
Section: Rack1 Signal Transductionmentioning
confidence: 99%